The Effect of COACHMAN Approach on Systolic and Diastolic Blood Pressure among Hypertensive Patients in Masohi Public Health Center Area - Usman Barus Ohorella; Irhamdi Ahmad; Abuzar Wakano (Jurnal Kesehatan Terpadu, 2025)
ABSTRACT Background: Blood pressure control is the main goal of hypertension management. However, many patients fail to achieve optimal levels due to poor adherence and lack of monitoring. This study analyzed the effect of COACHMAN (Community and Tech-Based Approach for Hypertension Self-Management) on systolic and diastolic blood pressure. Methods: A quasi-experimental pre–post test control group design was used with 30 hypertensive patients (15 intervention, 15 control). Blood pressure was measured before and after the intervention. Results: In the intervention group, 80% achieved normal systolic blood pressure post-intervention, compared to none before. Diastolic blood pressure improved to 100% normal after COACHMAN. In the control group, no significant changes were observed in either systolic or diastolic values. Conclusion: COACHMAN is effective in reducing systolic and diastolic blood pressure, highlighting its role in primary health care interventions. Keywords: hypertension, COACHMAN, systolic, diastolic